2016
DOI: 10.3171/2016.1.focus15608
|View full text |Cite
|
Sign up to set email alerts
|

Sport-related structural brain injury associated with arachnoid cysts: a systematic review and quantitative analysis

Abstract: Neurosurg Focus 40 (4):E9, 2016S port-related concussion (SRC) has emerged as a public health problem, affecting athletes of all ages and participation levels. 11,35,43 While SRC by definition includes normal imaging results, a minority of sportrelated head injuries result in structural brain injury. 3,18,19,84,85 These cases are often neurosurgical emergencies and can result in permanent neurological deficit and/or death. Recent literature has postulated that athletes with arachnoid cysts (ACs) demonstrate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…Various previous researches have conferred the risk of cSDH related with ACs. 3,4,7,8,12,13 The exact mechanism is still unclear. However, theories suggest that 1) veins within the wall could be hurt because of decreased compliance 2) veins without structural support of cyst wall are vulnerable 3) a slit-valve mechanism is formed, lead to increased pressure within the AC and vein rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Various previous researches have conferred the risk of cSDH related with ACs. 3,4,7,8,12,13 The exact mechanism is still unclear. However, theories suggest that 1) veins within the wall could be hurt because of decreased compliance 2) veins without structural support of cyst wall are vulnerable 3) a slit-valve mechanism is formed, lead to increased pressure within the AC and vein rupture.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The problem of AC as a cause of subdural bleeding is by no means not new, as noticed by Robinson as early as 1971. 6 Since then, several publications addressed the issue of AC coincidence with subdural hematoma in patients of exceptionally young age 6,16-20 (including case series analyses and exhaustive reviews 10, 21,22 ). Also, causal relationship between minor sports-related trauma and subsequent treatment of chronic subdural bleeding in AC bearing subjects has been previously suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the majority of case reports in which AC bleeds spontaneously or after minor trauma, some large, middle fossa cysts were described. 10, 21,22 Moreover, the size of the cyst has been identified as a risk factor for hematoma by Cress et al, 29 although Wester and Helland found that the temporal location rather than the size of the AC itself defines the risk of CSDH. 28 Both observations make our case even more unusual, since a small-size frontal convexity cyst can hardly be expected to bleed spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…However, theories suggest that 1) veins within the wall could be hurt because of decreased compliance 2) veins without structural support of cyst wall are vulnerable 3) a slit-valve mechanism is formed, lead to increased pressure within the AC and vein rupture. 9,[12][13][14] The compliance of the cyst is less than the normal brain.…”
Section: Discussionmentioning
confidence: 99%